Role of carbonyl reducing enzymes in the phase I biotransformation of the non-steroidal anti-inflammatory drug nabumetone in vitro - Skarydova, Lucie; Nobilis, Milan; Wsól, Vladimir (Xenobiotica; the fate of foreign compounds in biological systems, 2013)
1. Nabumetone is a clinically used non-steroidal anti-inflammatory drug, its biotransformation includes major active metabolite 6-methoxy-2-naphtylacetic acid and another three phase I as well as corresponding phase II metabolites which are regarded as inactive. One important biotransformation pathway is carbonyl reduction, which leads to the phase I metabolite, reduced nabumetone. 2. The aim of this study is the determination of the role of a particular human liver subcellular fraction in the nabumetone reduction and the identification of participating carbonyl reducing enzymes along with their stereospecificities. 3. Both subcellular fractions take part in the carbonyl reduction of nabumetone and the reduction is at least in vitro the main biotransformation pathway. The activities of eight cytosolic carbonyl reducing enzymes--CBR1, CBR3, AKR1B1, AKR1B10, AKR1C1-4--toward nabumetone were tested. Except for CBR3, all tested reductases transform nabumetone to its reduced metabolite. AKR1C4 and AKR1C3 have the highest intrinsic clearances. 4. The stereospecificity of the majority of the tested enzymes is shifted to the production of an (+)-enantiomer of reduced nabumetone; only AKR1C1 and AKR1C4 produce predominantly an (-)-enantiomer. This project provides for the first time evidence that seven specific carbonyl reducing enzymes participate in nabumetone metabolism.
Keywords: Liver; Subcellular Fractions; antiflogistika nesteroidní; Butanones; Kinetics; játra; Metabolic Detoxication, Phase I; Nabumetone; Alcohol Oxidoreductases; subcelulární frakce; lidé; Stereoisomerism; stereoizomerie; alkoholoxidoreduktasy; butanony; biokatalýza; Anti-Inflammatory Agents, Non-Steroidal; I. fáze biotransformace; biotransformace; Biotransformation; NADP; Biocatalysis; kinetika; nabumeton; Humans